PENGARUH MOTIVASI DAN KECERDASAN EMOSIONAL DIMODERASI SUPERVISI AKADEMIK TERHADAP KINERJA GURU (Studi pada smp Negeri di Kecamatan Ulujami Kabupaten Pemalang) - NOVI HIDAYATI, 1352020067; Liliana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze the influence of motivation and emotional intelligence moderated academic supervision of teacher performance in the Junior High School in the district of Pemalang Ulujami. The population in this study is Junior High School teacher in the district of Pemalang Ulujami as many as 125 teachers, primary data were collected using questionnaire instruments to measure variables using Likert scale. Hypothesis test used in this study is t-test at a significant level (a) 0,05.The results showed that motivation positive and significant impact on teacher performance, emotional intelligence a significant negative effect on the performance of teachers, academic supervision positve and significant impact onÂ the performance of teachers, academic supervision does not moderate the influence of emotional intelligence on the performance of teachers, academic supervision does not moderate the influence of motivation on teacher performance. Keywords: motivation, emotional intelligence, academic supervision, teacher performance.